Improvement of the Rheological and Filtration Properties of Drilling Mud Using the Syrian Clay (Journal of Engineering, 2020)
Drilling fluid properties and formulation play a fundamental role in drilling operations. The Classical water-based muds prepared from only the Syrian clay and water without any additives((Organic and industrial polymers) are generally poor in performance. Moreover, The high quantity of Syrian clay (120 gr / l) used in preparing drilling fluids. It leads to a decrease in the drilling speed and thus an increase in the time required to complete the drilling of the well. As a result, the total cost of drilling the well increased, as a result of an increase in the concentration of the solid part in the drilling fluid. In this context, our study focuses on the investigation of the improvement in drilling mud   Prepared from the Syrian clay by reducing the clay concentration to (50 gr / L). And compensate for the remaining amount (70 gr / l) of clay by adding (natural and industrial polymers) The rheological properties and filtration are measured at different concentrations of polymers .. In light of the experiments, we determine the polymers' concentrations that gave good results in improving the flow properties and controlling the Filter. It is polymers that have given good results:، HEC، HEC and Xanthan Gum  PAC and HEC، CMCHV، PolyAcryl Amid ، Xanthan Gum .